Biodiversity and distribution of freshwater microalgae from the black-water ecosystem of Rungan River, Central Kalimantan, Indonesia - LISWARA NENENG; KIKI LOUISA; YULIANA YULIANA; ZAHROTUN NAFISAH; DIAH RADINI NOERDJITO (Society for Indonesian Biodiversity, 2025)
Abstract. Neneng L, Louisa K, Yuliana, Nafisah Z, Noerdjito DR. 2025. Biodiversity and distribution of freshwater microalgae from the black-water ecosystem of Rungan River, Central Kalimantan, Indonesia. Biodiversitas 26: 1789-1798. The black-water ecosystem is strongly influenced by the physical appearance of peatlands, which include low pH, low Dissolved Oxygen (DO), high Dissolved Organic Carbon (DOC), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD), high tannins, and low nutrients. Identifying microalgae from this extreme environment enables us to isolate species that are naturally tolerant and exhibit unique features. This research aimed to explore, identify, and find information on the distribution of freshwater microalgae species from the black-water ecosystem in Rungan River of Central Kalimantan, Indonesia. This research also investigated the physicochemical parameters of the river to observe their impacts on microalgae distribution. There were 15 study sites in this research, including five main rivers (Rungan Rivers), five small rivers (Anjung, Tabatik, Panya, Karahang and Sahang), and five lakes (Humbang, Kuning, Petuk Uwah, Tahai Hulu and Rasau). Water samples were collected, and physicochemical parameters were measured and analyzed using standard protocols. The results showed that 59 species of freshwater microalgae were found in the study sites. These species belong to the classes Bacillariophyceae, Mediophyceae, Chlorophyceae, Zygnematophyceae, Charophyceae, Xantophyceae, Cyanophyceae, and Euglenoidea. Chlorella sp. and Clostridium sp. were discovered in all of study sites, while Botryococcus brownii and Spirulina sp. were only discovered at one site. The biodiversity index (H': 2.81) was included in the medium category. The highest abundance of microalgae species was found in lakes, and the lowest number was in the main rivers. The distribution of many microalgae (61%) in the black-water ecosystem was found in the pH range of 4.4-6.0. Besides, 71% of microalgae in the black-water ecosystem prefer to live at a temperature range of 28-32oC. Only Anabaena sp. was discovered at a temperature of 26-34oC. Principal Component Analysis (PCA) results showed that environmental parameters, including pH and nitrate, were the dominant factors that influenced the distribution and abundance of microalgae in this ecosystem.